Proteomic Analysis Reveals a Mitochondrial Remodeling of βTC3 Cells in Response to Nanotopography - Maffioli, Elisa; Galli, Alessandra; Nonnis, Simona; Marku, Algerta; Negri, Armando; Piazzoni, Claudio; Milani, Paolo; Lenardi, Cristina; Perego, Carla; Tedeschi, Gabriella (Frontiers in cell and developmental biology, 2020)
Recently, using cluster-assembled zirconia substrates with tailored roughness produced by supersonic cluster beam deposition, we demonstrated that β cells can sense nanoscale features of the substrate and can translate these stimuli into a mechanotransductive pathway capable of preserveing β-cell differentiation and function in vitro in long-term cultures of human islets. Using the same proteomic approach, we now focused on the mitochondrial fraction of βTC3 cells grown on the same zirconia substrates and characterized the morphological and proteomic modifications induced by the nanostructure. The results suggest that, in βTC3 cells, mitochondria are perturbed by the nanotopography and activate a program involving metabolism modification and modulation of their interplay with other organelles. Data were confirmed in INS1E, a different β-cell model. The change induced by the nanostructure can be pro-survival and prime mitochondria for a metabolic switch to match the new cell needs.Recently, using cluster-assembled zirconia substrates with tailored roughness produced by supersonic cluster beam deposition, we demonstrated that β cells can sense nanoscale features of the substrate and can translate these stimuli into a mechanotransductive pathway capable of preserveing β-cell differentiation and function in vitro in long-term cultures of human islets. Using the same proteomic approach, we now focused on the mitochondrial fraction of βTC3 cells grown on the same zirconia substrates and characterized the morphological and proteomic modifications induced by the nanostructure. The results suggest that, in βTC3 cells, mitochondria are perturbed by the nanotopography and activate a program involving metabolism modification and modulation of their interplay with other organelles. Data were confirmed in INS1E, a different β-cell model. The change induced by the nanostructure can be pro-survival and prime mitochondria for a metabolic switch to match the new cell needs.